2018
DOI: 10.1177/1464419318806801
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive sliding mode controller for the lateral control of articulated long vehicles

Abstract: Today, use of articulated long vehicles is surging. The advantages of using large articulated vehicles are that fewer drivers are used and fuel consumption decreases significantly. The major problem of these vehicles is inappropriate lateral performance at high speed. The articulated long vehicle discussed in this article consists of tractor and two semi-trailer units that widely used to carry goods. The main purpose of this article is to design an adaptive sliding mode controller that is resistant to changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…These noises are the Gaussian white type with mean zero. 27–29 According to the equations of the vehicle, the matrices x ( t ) and f ( x ( t ) , u ( t ) , t ) are as follows…”
Section: Simulation Resultsmentioning
confidence: 99%
“…These noises are the Gaussian white type with mean zero. 27–29 According to the equations of the vehicle, the matrices x ( t ) and f ( x ( t ) , u ( t ) , t ) are as follows…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The outcomes showed that the performance of the proposed controller in comparison to conventional controllers was enhanced, particularly in high speed lane change manoeuvre. 40 Autonomous vehicle technologies are complex systems. The systems can be divided into several parts and solved stepwise under different conditions.…”
Section: Control System Designmentioning
confidence: 99%
“…The applied lateral forces on the front and rear axles of the tractor and the axle of the semitrailer are substituted in three independent equations of the 3-DOF dynamic model of the AV. Accordingly, equations (36), (37), and (38) can be rewritten based on equations (39), (40), and (41). Finally, matrix form of the lateral dynamics of the tractor-semitrailer is presented in equation (42).…”
Section: Control System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Islam and He 27 presented a comparative study of multi-trailer articulated heavy-vehicle models, and also the proposed model was verified via a nonlinear model of the TruckSim software. In 2018, Esmaeili et al 28,29 used a long articulated vehicle, which was mathematically modeled using Newton’s equations in MATLAB software and verified by TruckSim software results. Also, these vehicles offer enhanced efficiency and emissions, but reduced low-speed maneuverability and high-speed stability.…”
Section: Dynamic Model Of the Vehicle Tire And Hydraulic Power Smentioning
confidence: 99%